Islamic Boarding Schools as Safe Spaces: Kiai’s Perspectives on Preventing Sexual Violence and Bullying Against Santri - Muhammad Faishol; Wasino Wasino; Fakhruddin Fakhruddin; Asrori Asrori (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study analyzes the role of kiai leadership in preventing sexual violence and bullying by conceptualizing pesantren as moral–institutional safe spaces. The study employs a qualitative approach based on purposive sampling and in-depth interviews with kiai at Pondok Pesantren Darussalam Dukuhwaluh, Banyumas (Central Java), and Pondok Pesantren Riyadlul ‘Ulum Wadda’wah Condong, Tasikmalaya (West Java), analyzed using a thematic–reflective method and contextualized with recent literature from reputable journals. Primary data were obtained from interviews with kiai, complemented by secondary data from institutional documents and relevant scholarly literature collected through document analysis.Findings indicate that pesantren as safe spaces are not primarily constructed through compliance with formal regulations, but rather through the integration of the kiai’s moral authority, layered caregiving systems, ethical management of power relations, and the transformation of seniority culture toward a culture of adab (ethical conduct) and santri protection. The novelty of this study lies in its formulation of the concept of a safe pesantren that emphasizes internal moral logic as a mechanism for violence prevention, while also revealing the limitations of approaches that rely excessively on personal authority figures. This article contributes to the development of pesantren education theory and enriches the discourse on violence prevention within religious-based institutions in Indonesia.